Role of House Flies in the Ecology of Enterococcus faecalis from Wastewater Treatment Facilities. - Zurek, Ludek; Scott, Harvey Morgan; Doud, C. W. (My University, 2014)
Enterococci are important nosocomial pathogens, with Enterococcus faecalis most commonly responsible for human infections. In this study, we used several measures to test the hypothesis that house flies, Musca domestica (L.), acquire and disseminate antibiotic-resistant and potentially virulent E. faecalis from wastewater treatment facilities (WWTF) to the surrounding urban environment. House flies and sludge fromfourWWTF (1–4) as well as house flies from three urban sites close to WWTF-1 were collected and cultured for enterococci. Enterococci were identified, quantified, screened for antibiotic resistance and virulence traits, and assessed for clonality. Of the 11 antibiotics tested, E. faecalis was most commonly resistant to tetracycline, doxycycline, streptomycin, gentamicin, and erythromycin, and these traits were intra-species horizontally transferrable by in vitro conjugation. Profiles of E. faecalis (prevalence, antibiotic resistance, and virulence traits) from each of WWTF sludge and associated house flies were similar, indicating that flies successfully acquired these bacteria from this substrate. The greatest number of E. faecalis with antibiotic resistance and virulence factors (i.e., gelatinase, cytolysin, enterococcus surface protein, and aggregation substance) originated from WWTF-1 that processed meat waste from a nearby commercial meat-processing plant, suggesting an agricultural rather than human clinical source of these isolates. E. faecalis from house flies collected from three sites 0.7–1.5 km away from WWTF-1 were also similar in their antibiotic resistance profiles; however, antibiotic resistance was significantly less frequent. Clonal diversity assessment using pulsed-field gel electrophoresis revealed the same clones of E. faecalis from sludge and house flies from WWTF-1 but not from the three urban sites close to WWTF-1. This study demonstrates that house flies acquire antibiotic-resistant enterococci from WWTF and potentially disseminate them to the surrounding environment.
Citation: Doud, C. W., Scott, H. M., & Zurek, L. (2014). Role of House Flies in the Ecology of Enterococcus faecalis from Wastewater Treatment Facilities. Retrieved from http://krex.ksu.edu
Keywords: E. faecalis; House flies; Antibiotic resistance; Wastewater treatment facilities